2017
DOI: 10.1142/s0218271817500936
|View full text |Cite
|
Sign up to set email alerts
|

Production of primordial gravitational waves in a simple class of running vacuum cosmologies

Abstract: The problem of cosmological production of gravitational waves is discussed in the framework of an expanding, spatially homogeneous and isotropic FRW type Universe with time-evolving vacuum energy density. The gravitational wave equation is established and its modified time-dependent part is analytically resolved for different epochs in the case of a flat geometry. Unlike the standard ΛCDM cosmology (no interacting vacuum), we show that gravitational waves are produced in the radiation era even in the context o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…been studied in detail in [25,42,51,52]. Whereas, the high order terms, which produce the inflationary stage, were studied by [53][54][55] among others.…”
Section: Running Vacuum From Renormalization Groupmentioning
confidence: 99%
“…been studied in detail in [25,42,51,52]. Whereas, the high order terms, which produce the inflationary stage, were studied by [53][54][55] among others.…”
Section: Running Vacuum From Renormalization Groupmentioning
confidence: 99%
“…In this kind of the models, Λ, instead of being a constant, is a function of the Hubble parameter H, and decays to matter and radiation [8]. It has been shown that the RVMs are suitable in describing the cosmological evolutions on both background and linear perturbation levels in the literature [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In these studies, the Hubble parameter H has been used to compose many forms of Λ =…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the cosmological constant Λ is described by a function of the Hubble parameter and decays to matter and radiation in the expansion of the universe [8]. It has been shown that the RVM is suitable in describing the cosmological evolution on both background and linear perturbation levels [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%